2014
DOI: 10.33151/ajp.11.6.128
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Paramedic Administration of Verapamil and Adenosine for the Treatment of Supraventricular Tachycardia: A Review of the Literature

Abstract: AbstractIntroductionAdenosine and verapamil are the most commonly used pharmacological agents to treat supraventricular tachycardia (SVT). This review aims to identify the effectiveness and safety of pre-hospital use of adenosine and verapamil by paramedics.MethodsA comprehensive electronic literature search was conducted. Studies of pre-hospital comparative effectiveness of adenosine and verapamil were included for further analysis. Studies where individual effectiveness of either verapamil or adenosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A review by Smith [16] comparing adenosine and verapamil administration for termination of SVT demonstrated that verapamil was more signi cantly effective for management of SVT than adenosine. Although, verapamil administration was associated with higher incidence and duration of side effects [16].…”
Section: Discussionmentioning
confidence: 99%
“…A review by Smith [16] comparing adenosine and verapamil administration for termination of SVT demonstrated that verapamil was more signi cantly effective for management of SVT than adenosine. Although, verapamil administration was associated with higher incidence and duration of side effects [16].…”
Section: Discussionmentioning
confidence: 99%